Model-Based Demography Essays on Integrating Data, Technique and Theory - Burch, Thomas K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Late in a career of more than sixty years, Thomas Burch, an internationally known social demographer, undertook a wide-ranging methodological critique of demography. This open access volume contains a selection of resulting papers, some previously unpublished, some published but not readily accessible [from past meetings of The International Union for the Scientific Study of Population and its research committees, or from other small conferences and seminars]. Rejecting the idea that demography is simply a branch of applied statistics, his work views it as an autonomous and complete scientific discipline. When viewed from the perspective of modern philosophy of science, specifically the semantic or model-based school, demography is a balanced discipline, with a rich body of techniques and data, but also with more and better theories than generally recognized. As demonstrated in this book, some demographic techniques can also be seen as theoretical models, and some substantive/behavioral models, commonly rejected as theory because of inconsistent observations, are now seen as valuable theoretical models, for example demographic transition theory. This book shows how demography can build a strong theoretical edifice on its broad and deep empirical foundation by adoption of the model-based approach to science. But the full-fruits of this approach will require demographers to make greater use of computer modeling [both macro- and micro-simulation], in the statement and manipulation of theoretical ideas, as well as for numerical computation. This book is open access under a CC BY license.
Part I: A Model-Based View of Demography: 1. Demography in a New Key: A Theory of Population Theory -- 2. Data, Models and Reality: The Structure of Demographic Knowledge -- 3. Computer Modeling of Theory: Explanation for the 21st Century -- 4. Computer Simulation and Statistical Modeling: Rivals or Complements? -- 5. Does Demography Need Differential Equations? Part II: Some Demographic Models Re-visited: 6. Theory, Computers and the Parametrization of Demographic Behavior -- 7. Estimating the Goodman, Keyfitz, Pullum Kinship Equations: An Alternative Procedure -- 8. The Life Table as a Theoretical Model -- 9. The Cohort-Component Projection Algorithm: Technique, Model and Theory -- 10. The Cohort-Component Projection Model: A Strange Attractor for Demographers Part III: Teaching Demography: 11. Teaching Demography: Ten Principles and Two Rationales -- 12. Teaching the Fundamentals of Demography: A Model-Based Approach to Family and Fertility,- 13. On Teaching Demography : Some Non-Traditional Guidelines -- Part IV: Conclusion:14 Conclusion -- Index.
Keywords: Demography; Population; Social sciences$1 (BStatistical methods.s; Science$1 (BPhilosophy.s; Sociology$1 (BMethodology.s; Population and Demography; Statistics in Social Sciences, Humanities, Law, Education, Behavorial Sciences, Public Policy; Philosophy of Science; Sociological Methods